Sinergi Guru Pendidikan Agama Islam dan Orangtua dalam Pembinaan Akhlak Peserta Didik - Chairun Nisa; Nurul Hasanah; Saifullah (Malewa: Journal of Multidisciplinary Educational Research, 2026)
Character development is a shared responsibility between schools and families. Effective collaboration between Islamic Education (PAI) teachers and parents plays a crucial role in fostering students’ moral character. This study aims to examine the forms of collaboration between PAI teachers and parents in promoting students’ moral development at SMP Negeri 1 Takengon. The study employed a qualitative descriptive approach, with data collected through observation, interviews, and documentation. The research participants consisted of two PAI teachers and three parents of students. Data were analyzed using the Miles and Huberman interactive theoryl, which includes data reduction, data display, and conclusion drawing. The validity of the data was ensured through source, technique, and time triangulation. The findings reveal that collaboration between PAI teachers and parents has been effectively implemented through direct consultation, home visits, communication via telephone and WhatsApp, formal correspondence, and parent-teacher meetings. These forms of collaboration facilitate information sharing, strengthen communication between schools and families, and support the continuity of students’ moral development both at school and at home.